A Film Bulk Acoustic Resonator-Based Sensor with AlN Piezoelectric Material for Detecting Ethanol and Acetone - Jieyi Zhu; Meiyan Feng; Guofu Lian (Shock and Vibration)
Measurement of a volatile solution is essential for laboratory safety and hospital clinic safety. In this paper, we present an ethanol-sensing and acetone-sensing device using an AlN piezoelectric material-based film bulk acoustic resonator (FBAR). In order to realize volatile solution sensing, the AlN-based FBAR was designed, fabricated, and characterized. In our sensor structure, the upper electrode is a Ti/Au (30 nm/150 nm) composite electrode, the bottom electrode is Mo material with 150 nm thickness, and the piezoelectric sensing material is 0.8 μm thickness AlN. We conducted the experiment of ethanol measurement and acetone measurement by using this FBAR detector on the probe station within the vector network analyzer. The resonance frequency of the FBAR detector decreased as the concentration of ethanol increases, while under the circumstance of acetone concentration increasing, the detector’s response is the opposite. The sensing mechanisms of both ethanol measurement and acetone measurement are discussed in this paper, demonstrating that this FBAR detector could be able to distinguish acetone from ethanol due to different sensing mechanisms.